Duality Unresolved and Darwinian Dilemmas - Tullis, Anson (Stance: an international undergraduate philosophy journal, 2015)
By using Sharon Street’s Darwinian Dilemma, Katarzyna de Lazari-Radek and Peter Singer attempt to show that Sidgwick’s duality of practical reason, whereby an agent has equal reason to act in their own interests or act impartially for the benefit of all, is not actually a duality; rather, reasons for action are solely impartial due to the unreliability of intuitions favoring self-interested behavior. I argue that Lazari Radek and Singer fail to accomplish their goal. I argue that Singer has previously provided an account of impartiality that makes it just as unreliable on the same grounds as self-interested tendencies. Sidgwick’s duality remains unresolved.